Батько українського театру (до 170-річчя від дня народження видатного драматурга, актора і режисера Марка Кропивницького) - Аксьом, А.А. (Архіви України, 2010)
Висвітлено склад архівних зібрань з фондів ЦДАМЛМ України, присвячених життю і творчості фундатора українського театрального мистецтва XIX – поч. XX ст. Освещен состав архивных собраний из фондов ЦДАМЛМ Украины, посвященных жизни и творчеству основателя украинского театрального искусства XІX – нач. XX ст. The review tells about of the archival collections of Central State Archive Museum of Literature and Arts of Ukraine, denoted to the life and art activity of M. Kropyvnyts’kyi, the founder of the Ukrainian theatrics in XIX – beginning of XX century. There is highlighted the feat of “father of the ukrainian theatre” in the conditions of prohibition by tsarism of the Ukrainian word and culture.